Ecotourist attitude homogeneity in biodiversity hotspots: A multi-dimensional sustainability analysis from Meghalaya, India - Paramjeet Kumar (Borneo Novelty Publishing, 2026)
Purpose – This study aims to examine the homogeneity of ecotourists’ attitudes toward sustainability and conservation behaviour in biodiversity-rich destinations, and to analyse the relationships between demographic characteristics, travel patterns, and five sustainability constructs: Nature-based Sustainable Development (NSD), Responsible Nature Tourism (RN), Knowledge Factors (KF), Environmental Consciousness (E), and Other Tourism Practices (OTP). Design/Methodology/Approach – A quantitative survey was conducted among 300 ecotourists visiting nature-based destinations in Meghalaya, a recognized biodiversity hotspot in India. The study utilized validated measurement scales and applied statistical techniques including factor analysis, reliability testing, and comparative analysis to assess sustainability constructs and behavioural patterns.Findings – The results identify five underlying sustainability factors with high reliability (α = 0.827–0.931). Contrary to expectations, no significant demographic differences were found in sustainability attitudes (p > 0.05), indicating a homogeneous conservation orientation among ecotourists. All constructs scored above the scale midpoint, reflecting strong pro-environmental attitudes. Environmental consciousness emerged as the most influential factor (M = 4.371), with moderate positive correlations among constructs (r = 0.099–0.207). The strongest relationship was observed between knowledge factors and environmental consciousness (r = 0.207, p < 0.001).Originality/Value – This study challenges conventional assumptions of demographic segmentation by demonstrating uniform sustainability attitudes among ecotourists in biodiversity hotspots. It highlights the role of destination attributes in attracting environmentally conscious tourists and provides insights for developing conservation-oriented ecotourism strategies that support sustainable development and community empowerment.